Metal triflate promoted synthesis of naphthalenes. Issue 47 (6th June 2017) - Chan, Chieh-Kai; Wang, Heui-Sin; Tsai, Yu-Lin; Chang, Meng-Yang
Abstract : A synthetic route to derive the skeleton of naphthalenes starting with isovanillin is described with modest total yields via the key transformation of metal triflate-mediated intramolecular benzannulation of o -formyl or o -benzoyl allylbenzenes in MeNO2 at rt. Abstract : A synthetic route to derive the skeleton of naphthalenes starting with isovanillin is described with modest total yields via the key transformation of metal triflate-mediated intramolecular benzannulation of o -formyl or o -benzoyl allylbenzenes in MeNO2 at rt.